The contested common pool resource: Ground water use in urban Kathmandu, Nepal - Shrestha, Shobha (Geographical Journal of Nepal, 2017)
Groundwater has always played a critical role in meeting the water demands of traditionally water-short areas of urban Kathmandu. Studies show that ground water level is depleting and is under immense pressure due to over-extraction.The current study focuses on existing situation of ground water availability and use in urban Kathmandu, conflicts among households for ground water use and changing social setting and policy implementation.The study found that the traditional culture of using public well and sharing and optimizing groundwater resource is gradually fading due to scarcity of water. Private deep wells are being constructed inside house for household use altering traditional social setting of a public well and culture of sharing public resource is declining. There is no authority and policy to control and monitor the ground water extraction for private use. The increasing number of groundwater extraction, uncontrolled and unregulated use for private and commercial use has contested the use of common pool resource and traditional social setting. The Geographical Journal of Nepal Vol. 10: 153-166, 2017